Determinants of automatic age and race bias: ingroup-outgroup distinction salience moderates automatic evaluations of social groups - Heitmann, Stephanie; Reichardt, Regina (Frontiers in Psychology, 2024)
The present research demonstrates that ingroup-outgroup distinction salience moderates automatic intergroup bias (i.e., a more positive evaluation of the ingroup relative to the outgroup). In two experiments, we manipulated the salience of participants’ social identity based on age vs. race, respectively. Young White participants exhibited higher automatic race bias when their racial identity (i.e., White in contrast to Black) was salient, and higher automatic age bias when their age identity (i.e., young in contrast to old) was salient. Going beyond previous research, we show that it is sufficient to direct participants’ attention to their ingroup-identity in contrast to the respective outgroup to cause changes in automatic intergroup bias. This is important because it provides a strong test of the hypothesis that ingroup-outgroup distinction salience moderates automatic intergroup bias.